A Multinational Company Problem: Infiltrating Into the Clusters to Gain Competitive Edge in the Traditional Markets - KOC, Murat; KOC, Fatih (International Review of Management and Marketing, 2014)
This paper is concerned with one of the main challenges of the Multinational Companies which they face in the traditional and thus in local markets. Multinational Companies aims to gain competitive advantage through differentiation in terms of their globalization strategy. However, in the local markets where the organic relationship of firms are more designed in local habits, and markets react with stable consumer behaviors, it gets harder to enter into market and drive a competitive edge. This paper aims to understand the reasons of this challenge, the analysis of resistance of traditional markets, successful sample breaking into local market and the strategy around it. Keywords: Multinational Company; Competitive Edge; Traditional Markets; Clusters JEL Classifications: M00; M10